High Work Motivation with Low Corruption: Building Integrity Through Employee Engagment in PT. KAI - Tri Panca Titis Arbiansyah; Emha Zainul Mukminin (Research Synergy Foundation, 2025)
This study aims to analyze the effect of work motivation on employee engagement with integrity as a mediating variable, as well as to examine its implications for the development of an anti-corruption culture among permanent employees of PT. KAI. The study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 224 permanent KAI employees. The data were analyzed using Structural Equation Modeling (SEM) with the assistance of LISREL software. The results indicate that the structural model with integrity as a mediator meets the goodness-of-fit criteria. Work motivation does not have a direct effect on employee engagement, but it requires integrity as an ethical foundation. Furthermore, work motivation has a positive influence on integrity, which in turn strengthens employees’ attachment to their work. However, integrity alone does not have a direct impact on employee engagement and requires the support of motivational and organizational factors. These findings suggest that motivation without integrity may lead to opportunistic behavior. The combination of motivation and integrity fosters stronger, more productive, and ethically grounded employee engagement. Practically, this study highlights the importance of strengthening work motivation framed by integrity to build a sustainable anti-corruption culture within state-owned enterprises.